Selective Encoding: Reducing the Burden of Transcription for Digital Musicologists - Saccomano, Mark; Rosendahl, Lisa; Lewis, David; Hankinson, Andrew; Kepper, Johannes; Page, Kevin; Shibata, Elisabete (Journal of the Text Encoding Initiative)
Keywords: DigitaleEdition

Exploring the Genesis of Complex Music Manuscripts - Kepper, Johannes; Sänger, Richard York; Voigt, Jan-Peter (Journal of the Text Encoding Initiative)

Zu den Anforderungen einer musikalischen Stilometrie - Kepper, Johannes
This is the extended abstract for my conference paper from the 2020 DHd Conference in Paderborn, along with the slides and moderator notes from the corresponding presentation.

MEI: The Music Encoding Initiative Guidelines (PDF)
PDF versions of the Music Encoding Initiative Guidelines 5.0 [2023]: This version represents the 5.0 release of the Music Encoding Initiative Guidelines.

A New Conceptual Model for Musical Sources and Musicological Studies - Shibata, Elisabete; Lewis, David; Saccomano, Mark; Kepper, Johannes; Page, Kevin (Proceedings of the Music Encoding Conference 2022)
We present a new multi-layered, conceptual model for associating musical source materials to musicological arguments. We describe our proposal for operationalizing these concepts through a framework for musical annotation which we have implemented using RDF. Briefly stated, this model shows how portions of digitized data in various files and formats can be identified, selected, labelled, and compared.
Keywords: BitH; Linked Data

Supporting Musicological Investigations With Information Retrieval Tools: An Iterative Approach to Data Collection - Lewis, David; Shibata, Elisabete; Hankinson, Andrew; Kepper, Johannes; Page, Kevin R.; Rosendahl, Lisa; Saccomano, Mark; Siegert, Christine
Digital musicology research often proceeds by extending and enriching its evidence base as it progresses, rather than starting with a complete corpus of data and metadata, as a consequence of an emergent research need. In this paper, we consider a research workflow which assumes an incremental approach to data gathering and annotation. We describe tooling which implements parts of this workflow, developed to support the study of nineteenth-century music arrangements, and evaluate the applicability of our approach through interviews with musicologists and music editors who have used the tools. We conclude by considering extensions of this approach and the wider implications for digital musicology and music information retrieval.
Keywords: BitH; Linked Data

Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Beethoven in the House: Digital Studies of Domestic Music Arrangements - Page, Kevin R.; Kepper, Johannes; Siegert, Christine; Hankinson, Andrew; Lewis, David (Music Encoding Conference Proceedings 2021)
Performance of music in the home was the means by which most works were received before the advent of audio recordings and broadcasts, yet the notation sources that form our primary record of this culture have not been the subject of comprehensive or methodical study. Choices made by arrangers adapting music for domestic consumption – of instrumentation, abbreviation, or simplification – reflect the musical life of the 19th century, and can inform our understanding alongside contemporary accounts such as newspapers, adverts, and diaries. This position paper gives the background, motivation, and proposed approach of research currently being undertaken within the Beethoven in the House project. This will include a study of Steiner editions of Beethoven’s 7th and 8th Symphonies and Wellingtons Sieg, making a detailed comparison between arrangements, systematically identifying a core common to multiple versions, and asking if this reflects the stated values of the publisher. A second survey will look for patterns across a larger sample of lesser-known and poorly catalogued scores, collating emergent indicators of arrangers’ motivations within a narrative of the domestic market – the music industry of its day. Both studies will innovate digital methods which characterise arrangements as music encodings, including ‘sparse’ approaches to notation and annotation.
Keywords: BitH; mec-proceedings; mec-proceedings-2021

Encoding Genetic Processes II - Cox, Susanne; Kepper, Johannes (Music Encoding Conference Proceedings 2021)

A model for annotating musical versions and arrangements across multiple documents and media - Lewis, David; Shibata, Elisabete; Saccomano, Mark; Rosendahl, Lisa; Kepper, Johannes; Hankinson, Andrew; Siegert, Christine; Page, Kevin (9th International Conference on Digital Libraries for Musicology)
Keywords: BitH

MusicDiff – A Diff Tool for MEI - Herold, Kristin; Kepper, Johannes; Mo, Ran; Seipelt, Agnes Regina (Music Encoding Conference Proceedings 2020)
For musicologists, the collation of multiple sources of the same work is a frequent task. By comparing different witnesses, they seek to identify variation, describe dependencies, and ultimately understand the genesis and transmission of (musical) works. Obviously, the need for such comparison is independent from the medium in which a musical work is manifested. In computing, comparing files for difference is a common task, and the well-known Unix utility diff is almost 46 years old. However, diff, like many other such tools, operates on plain text. While many music encoding formats based on plain text exist, formats used in the field of Digital Humanities are typically based on XML. There are dedicated algorithms for comparing XML as well, but they only focus on the syntax of XML, but not the semantic structures modelled into such standards as MEI. MEI seeks to describe musical structures, and the XML syntax is just a means to express those structures. A diff tool for music should focus on comparing musical structures, but not the specifics of their serialization into a file format. In Beethovens Werkstatt, a 16-year project focussed on exploring the concepts and requirements of digital genetic editions of music, based on and arguing with examples from Ludwig van Beethoven, a case-bound diff tool for music was developed. The following paper discusses how that specific tool can be generalized, and which use cases such a tool may support.
Keywords: mec-proceedings; mec-proceedings-2020

Music Encoding Conference Proceedings 2015, 2016 and 2017
Conference proceedings of the Music Encoding Conferences 2015, 2016 and 2017 with Introduction by Giuliano Di Bacco
Keywords: mec-proceedings; mec-proceedings-2016; mec-proceedings-2015; mec-proceedings-2017

Wie? Was? Entsetzen! Lessons Learned from the Freischütz Digital Project - Kepper, Johannes (Music Encoding Conference Proceedings 2015, 2016 and 2017)
The Freischütz Digital project (FreiDi) was one of the pioneer projects employing MEI in large scale. It did not only try to encode a huge quantity of music material, it also sought to capture as many aspects of the available sources as possible, effectively creating data of almost unrivaled richness. This paper discusses the outcomes of and experiences made in the FreiDi project.
Keywords: mec-proceedings; mec-proceedings-2016

Zu den Herausforderungen der Softwareentwicklung im Projekt Beethovens Werkstatt: Dokumentation und Zwischenbilanz (2014–2017) - Kepper, Johannes
This report summarizes technical concepts of the Beethovens Werkstatt project, discussing various prototypes and the technical architectures used. The original version at https://beethovens-werkstatt.de/softwareentwicklung-2017/ includes videos not available in the PDF version published on Zenodo.
Keywords: Musicology; Digital humanities

Was ist eine Digitale Edition? Versuch einer Positionsbestimmung zum Stand der Musikphilologie im Jahr 2017 - Kepper, Johannes; Pugin, Laurent (Musiktheorie (Zeitschrift für Musikwissenschaft))

Freischütz Digital: data-music, The Academy 2017 Release - Kepper, Johannes
This is a copy of the Freischütz Digital/data-music repository, which is meant for long-term preservation. A description of the dataset can be found in the readme.md file.

Music Encoding Initiative Guidelines Version 3.0.0 - Kepper, Johannes; Roland, Perry D.

Die Spuren des Digitalen. Über die Nachnutzbarkeit digitaler Inhalte - Kepper, Johannes; Hartwig, Maja („Ei, dem alten Herrn zoll’ ich Achtung gern’“. Festschrift für Joachim Veit zum 60. Geburtstag)

Expression beyond Scope: How FRBR and MEI fit together - Kepper, Johannes; Richts, Kristina (IAML Congress Programme with abstracts)

Music Encoding Conference Proceedings 2013 and 2014 - Kepper, Johannes; Roland, Perry D.